Smart Radio - Building Music Radio On the Fly - Hayes, Conor; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2000)
This paper describes the development of a networked music application at Trinity College Dublin. Smart Radio is a web based client-server application which uses streaming audio technology and collaborative recommendation techniques to allow users build, manage and share music programmes. While it is generally acknowledged that music distribution over the web will dramatically change how the music industry operates, there are few prototypes available to demonstrate how this could work in an managed way. The Smart Radio approach is to have people manage their music resources by putting together personalised music programmes. These programmes can then be swapped using techniques of collaborative recommendation to find similarities between users. The smart radio system currently runs within the Computer Science Intranet with permission from the Irish Music Rights Organisation (IMRO). It is a prototype system for an "always on" high bandwidth Internet connection such as ADSL.
Keywords: Computer Science